Another Worldview Is Possible: Grassroots Social Movements and the ‘Great Work’ - Hernandez, Andreas (Journal for the Study of Religion, Nature and Culture, 2018)
Observers such as Thomas Berry and David Korten have proposed that the contemporary 'Great Work' is to tell new stories, embodied in practical new politics and economics, to navigate the deep cultural and institutional transformations necessary for human communities to survive and